2015
DOI: 10.1080/0309877x.2015.1014317
|View full text |Cite
|
Sign up to set email alerts
|

Making productive use of exemplars: Peer discussion and teacher guidance for positive transfer of strategies

Abstract: Discussion of exemplars of student work is a productive means of explaining tacit knowledge and guiding students into the requirements of academic writing. Through two cycles of action research in a postsecondary institution in Hong Kong, this study examines how exemplars can be used to enhance student understanding of quality and to promote positive transfer of strategies and skills from exemplars to assessment task. Interventions included peer discussion, teacher-led interaction and student mini-presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 17 publications
(32 reference statements)
0
38
0
2
Order By: Relevance
“…Earlier work done by Orsmond et al (2002) identified that student discussion regarding a range of exemplars without the revelation of grades aided in understanding notions of quality. To and Carless (2015) more recently have advocated for a 'dialogic' approach involving student participation in different types of discussion, as well as teacher guidance. However, teachers may need to reserve their own evaluative judgement to allow students to co-construct understandings of quality (Carless and Chan 2016).…”
Section: Exemplarsmentioning
confidence: 99%
“…Earlier work done by Orsmond et al (2002) identified that student discussion regarding a range of exemplars without the revelation of grades aided in understanding notions of quality. To and Carless (2015) more recently have advocated for a 'dialogic' approach involving student participation in different types of discussion, as well as teacher guidance. However, teachers may need to reserve their own evaluative judgement to allow students to co-construct understandings of quality (Carless and Chan 2016).…”
Section: Exemplarsmentioning
confidence: 99%
“…The inclusion of more local content in my module is another approach I should like to explore, with examples, short videos and case studies related to public health in China, so that they may able to distinguish how public health systems in Asian and Western countries differ from each other. By means of pedagogical context in assessment tasks, I can help to improve the student learning experience (Jayakumar, 2008;To and Carless, 2016). I acknowledge that, when I design the role play activity again, I should like to set more initial ground rules, whilst also giving more flexibility to the students.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment exemplars provide opportunities for students and teachers to explore assessment task requirements. Most recently, To and Carless (2015) and To and Liu (2017) reported on studies that focussed on the "dialogic use of exemplars" which they described as student participation in discussion to maximize the potential of analyzing exemplars. They also noted the importance for the teacher that "teacher guidance serves to explicate the characteristics of good quality work and to increase students' critical awareness of the differences between exemplars and their own writing" (p. 1).…”
Section: Literature Reviewmentioning
confidence: 99%